Social learning in the medial prefrontal cortex - Apps, M; Sallet, J (Elsevier, 2017)
The ACC, and neighbouring areas, are among the most controversial and investigated brain areas in cognitive neuroscience. Despite the wealth of studies, there has been a significant absence of studies recording from the gyrus of the ACC (ACCg). In their recent study Hill and colleagues provide a rare examination of the properties of the ACCg. We highlight the emerging role of this region in signalling the key computations that drive social learning processes.